Let
x------> the number of multiple choice question
y------> the number of free response question
we know that
-----> equation A
-----> equation B
Substitute equation B in equation A
Find the value of x
therefore
the answer is
the number of multiple choice question are
the number of free response question are
The answer would be
B) 1
hope this helps!
Answer:
-6x - y = 27 = x=
−1
/6
y+
−9
/2
3x + 8y = 9 = x=
−8
/3
y+3
Step-by-step explanation:
be more specific and space out the equations next time please, i didn't know what you wanted me to do. but i solved them.
brainliest please?